Efficacy and tolerability of quinidine as salvage therapy for monomorphic ventricular tachycardia in patients with structural heart disease. (6th October 2021) - Deshmukh, Amrish; Larson, John; Ghannam, Michael; Saeed, Mohammed; Cunnane, Ryan; Ghanbari, Hamid; Latchamsetty, Rakesh; Crawford, Thomas; Jongnarangsin, Krit; Pelosi, Frank; Chugh, Aman; Oral, Hakan; et al.
Abstract: Introduction: Quinidine is an effective therapy for a subset of polymorphic ventricular tachycardia and ventricular fibrillation (VF) syndromes; however, the efficacy of quinidine in scar‐related monomorphic ventricular tachycardia (MMVT) is unclear. Methods and Results: Between 2009 and 2020 a single VT referral center, a total of 23 patients with MMVT and structural heart disease (age 66.7 ± 10.9, 20 males, 15 with ischemic cardiomyopathy, mean LVEF 22.2 ± 12.3%, 9 with left ventricular assist device [LVAD]) were treated with quinidine (14 quinidine gluconate; 996 ± 321 mg, 8 quinidine sulfate; 1062 ± 588 mg). Quinidine was used in combination with other antiarrhythmics (AAD) in 19 (13 also on amiodarone). All patients previously failed >1 AAD (amiodarone 100%, mexiletine 73%, sotalol 32%, other 32%) and eight had prior ablations (median of 1.5). Quinidine was initiated in the setting of VT storm despite AADs (6), inability to tolerate other AADs (4), or recurrent VT(12). Ventricular arrhythmias recurred despite quinidine in 13 (59%) patients at a median of 26 (4–240) days after quinidine initiation. In patients with recurrent MMVT, VT cycle length increased from 359 to 434 ms ( p = .02). Six (27.3%) patients remained on quinidine at 1 year with recurrence of ventricular arrhythmias in all. The following adverse effects were seen: gastrointestinal side effects (6), QT prolongation (2), rash (1), thrombocytopenia (1), neurologic side effects (1). One patient discontinued due to cost. Conclusion: Quinidine therapy has limited tolerability and long‐term efficacy when used in the management of amiodarone‐refractory scar‐related MMVT.